2012
DOI: 10.1186/1471-2369-13-48
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension resistant to antihypertensive agents commonly occurs with the progression of diabetic nephropathy in Japanese patients with type 2 diabetes mellitus: a prospective observational study

Abstract: BackgroundWe investigated 1) the frequency of hypertension in patients with type 2 diabetes graded by the new classification of chronic kidney disease (CKD) reported by the Kidney Disease: Improving Global Outcomes (KDIGO) and 2) the number of antihypertensive agents needed to achieve treatment goals using a prospective observational study.MethodsA population of 2018 patients with type 2 diabetes mellitus was recruited for the study. The CKD stage was classified according to the eGFR and the urinary albumin ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
2
8
2
Order By: Relevance
“…Furthermore, it might be necessary to consider the vascular protective effects, as well as the blood pressure lowering effect when selecting antihypertensive agents for these patients. Approximately half of the patients required two or more antihypertensive agents in the present study, as previously reported [8,9]. The number of antihypertensive agents being used in our study was similar to that in a report investigating the status of blood pressure in 466 diabetic and 2934 nondiabetic Japanese patients with hypertension [21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, it might be necessary to consider the vascular protective effects, as well as the blood pressure lowering effect when selecting antihypertensive agents for these patients. Approximately half of the patients required two or more antihypertensive agents in the present study, as previously reported [8,9]. The number of antihypertensive agents being used in our study was similar to that in a report investigating the status of blood pressure in 466 diabetic and 2934 nondiabetic Japanese patients with hypertension [21].…”
Section: Discussionsupporting
confidence: 88%
“…The risk for cardiovascular events synergistically increases in patients with both diabetes mellitus and hypertension [5]. Although the target blood pressure is recommended to be less than 130/80 mmHg in order to prevent diabetic vascular events [6,7], hypertension is often resistant to treatment in patients with type 2 diabetes mellitus [8,9]. It is difficult to control blood pressure using single agents, and combination therapy is needed in many diabetic patients with hypertension [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD, chronic kidney disease; eGFR, estimated glomerular filtration rate. Moreover, in a relatively small cohort of Japanese patients with type 2 diabetes, an increased frequency of hypertension requiring more drugs to be treated has been recently shown to be coupled with CKD progression [30]. ÃÃ P < 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant difference in older and younger age in CKD with T2D and CKD without T2D. There is no significant difference between age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Systolic blood pressure was also higher in CKD patients with T2D than in those without T2D (P <0.001).…”
Section: Resultsmentioning
confidence: 91%